RESPON MASYARAKAT DESA SITIMULYO TERHADAP PENGELOLAAN TEMPAT PEMBUANGAN AKHIR SAMPAH (TPA) PIYUNGAN BANTUL YOGYAKARTA - Sulistyaningsih Sulistyaningsih (Jurnal Sosiologi Reflektif, 2015)
The Problem of waste, especially the domestic one, needs to be addressed wisely. Up to now, the management of domestic waste is based on sanitary landfil system, which requires all domestic wastes to be managed, condensed, and buried as prescribed in Perda No.3 Tahun 2013 on the Management of Domestic Waste and Other Similar Wastes. The Practice of this bylaw could not be optimized yet because the Final Disposal at Piyungan is only operated in every three days, not in a daily basis. Final Waste Disposal (TPA) of Piyungan located in Sitimulyo Village. It established in 1995 and started their operation in 1996. The location of TPA Piyungan which is not far from the villagers’ settlement, especially those who live in Ngablak Hamlet, Sitimulyo Village, has resulted on various comments among the villagers on the existence of the TPA. Some villagers supported the existence of the TPA based on some economic benefis. Others are tend to reject the TPA based on air and water pollutions of the TPA. The aim of this research is to map the response of the villagers of Sitimulyo and the policy of the Village government on the issue of the management of TPA Piyungan. The data in this research arecollected through in-depth interview, newspapers, and other research reports. This research uses Blummer’s symbolic interactionism theory to analyze the data. This research fids several important issues: First, since its operation in 1995, TPA Piyungan has resulted on various responses among the villagers. Those who support the TPA usually benefied economically, while those who are not have any benefi tend to reject the existence of the TPA. Second, The Sitimulyo government is on the neutral position. They will ask the provincial governmen of Yogyakarta to close the TPA if most of the villagers want to do so. They are also ready to preserve the existence of the TPA, if it is based on the majority voices of the villagers.